Hospitalized Children With Common Human Coronavirus Clinical Impact of Codetected Respiratory Syncytial Virus and Rhinovirus. Issue 3 (4th January 2022) - Heimdal, Inger; Valand, Jonas; Krokstad, Sidsel; Moe, Nina; Christensen, Andreas; Risnes, Kari; Nordbø, Svein Arne; Døllner, Henrik
Abstract : Background: The clinical impact of common human coronavirus (cHCoV) remains unclear. We studied the clinical manifestations of pediatric cHCoV infections and the possible modifying effects of codetected human rhinovirus (RV) and respiratory syncytial virus (RSV). Methods: We used data from an 11-year-long prospective study of hospitalized children with community-acquired respiratory tract infections. Nasopharyngeal aspirates were analyzed with real-time polymerase chain reaction assay for cHCoV OC43, NL63, HKU1 and 229E, and 15 other respiratory viruses. We assessed disease severity based on the clinical factors hospitalization length, oxygen requirement, other respiratory support and supplementary fluids. Results: cHCoV was detected in 341 (8%) of 4312 children. Among 104 children with single cHCoV detections, 58 (56%) had lower respiratory tract infection (LRTI) and 20 (19%) developed severe disease. The proportion with severe disease was lower among single cHCoV detections compared with single RSV detections (338 of 870; 39%), but similar to single RV detections (136 of 987; 14%). Compared with single cHCoV, codetected cHCoV-RSV was more often associated with LRTI (86 of 89; 97%) and severe disease (adjusted odds ratio, 3.3; 95% confidence interval: 1.6–6.7). LRTI was more frequent in codetected cHCoV-RV (52 of 68; 76%) than single cHCoV, but the risk of severe disease was lower (adjusted odds ratios, 0.3; 95% confidence interval: 0.1–1.0). Conclusions: cHCoV was associated with severe LRTI in hospitalized children. Viral codetections were present in two-thirds. Codetections of cHCoV-RV were associated with lower proportions of severe disease, suggesting a modifying effect of RV on HCoV.